2019
DOI: 10.1016/j.cmi.2018.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Microbiologic epidemiology depending on time to occurrence of prosthetic joint infection: a prospective cohort study

Abstract: Considering the minority amount of GNB in late postoperative PJI, the empirical use of a broad-spectrum β-lactam should be reconsidered, especially when a two-stage exchange is planned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
3
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 23 publications
6
72
3
5
Order By: Relevance
“…Benito and colleagues focused on the influence of route of acquisition and time after surgery on the microbiology of PJI [22]. In their prospective study, Triffault-Fillit and colleagues described the microbiology of PJI depending on time to occurrence [23]. These two studies suggest that few or no Gram-negative bacilli are isolated from late PJI.…”
Section: Discussionmentioning
confidence: 99%
“…Benito and colleagues focused on the influence of route of acquisition and time after surgery on the microbiology of PJI [22]. In their prospective study, Triffault-Fillit and colleagues described the microbiology of PJI depending on time to occurrence [23]. These two studies suggest that few or no Gram-negative bacilli are isolated from late PJI.…”
Section: Discussionmentioning
confidence: 99%
“…4). [10]. вне зависимости от чувствительности штаммов стафилококков к метициллину изоляты S. epidermidis значимо чаще были устойчивы к большинству изученных антибиотиков.…”
Section: материал и методыunclassified
“…несмотря на то, что наиболее частыми в России возбудителями нозокомиальных инфекций являются представители сем. enterobacteriaceae, P. aeruginosa и Acinetobacter sp., на долю которых приходится 43,1, 19,6 и 14,4% всех выделенных бактериальных возбудителей госпитальных инфекций [18-20], их участие в этиологии ортопедических имплантат-ассоциированных инфекций не столь велико и, по данным различных авторов, не превышает в совокупности 10-35% [9,10,21,22]. в нашей работе в общем спектре возбудителей ИаИ выявлено снижение частоты выделения Acinetobacter sp.…”
Section: материал и методыunclassified
See 1 more Smart Citation
“…Empirical antibiotic treatment of early PJIs include coverage of vancomycin was recommended until de nitive culture results become available [20]. In a prospective cohort study of microbiologic epidemiology of PJI, the results revealed 28.9% of S. aureus, 28.6% of CNS, 14.1% of Enterobacteriaceae and 13.1% of streptococci [21].…”
Section: Discussionmentioning
confidence: 99%